Implementasi Metode Analisis Menggunakan NVivo Dalam Penelitian Kualitatif - Hartono Hartono; Jose Da Silva; Francisco Da Costa; Donny Melianto; Made Suparta (Fakultas Ekonomi Program Studi Akuntansi Universitas 45 Surabaya, 2025)
Hartono, 2025. Analysis Using Nvivo In Qualitative Research. Doctoral Program, 17 Agustus 1945 University, Surabaya. Qualitative research plays an important role in exploring social phenomena in depth, but often faces challenges in managing and analyzing complex data. NVivo is a software solution designed to help researchers conduct qualitative data analysis systematically and efficiently. This paper discusses the use of NVivo in analyzing in-depth interview data on public perceptions of public transportation policies. With a descriptive approach and case studies, this paper shows how NVivo facilitates the process of coding, category creation (nodes), pattern searching (query), and data visualization. The results of the analysis show that NVivo improves accuracy, efficiency, and facilitates collaboration in qualitative research. Thus, NVivo is recommended as an important tool in improving the quality and validity of social research results.